As novas dinâmicas socioespaciais no espaço urbano da cidade de Cajazeiras - PB, como resultantes da presença do ensino superior - Costa Filho, Joaquim Alves da (2018)
This research sought to address higher education government of Fernando Henrique Cardoso – FHC (1995-2002), and Luiz Inácio Lula da Silva (2003-2010), with regard to the process of expansion, extension and internalization of higher education (HELs), Brazilian public and private, as well as the courses from public policies implemented by these managements for those managements for the promotion and development of this subsector. That said, the general objective of this study it’s to analyze the dynamics socioespaciais in the city of Brazil, as resulting from the presence of the public and private higher education. Higher education in cajazeirense territory in the early 1970, however, just came to develop and consolidate from the decade of 1980 and the first decade of the years 2000, respectively, depending on the implementation of the teacher training Center of the Federal University of Paraíba (CFP/UFPB), in 1980, and with the expansion and extension of IES and subsequent courses to the year 2006. The methodology of approach and procedures assumed continuous and contradictory changes revealed in the form and content of the phenomena deployed in the city of Brazil, as a reflection of the higher education subsector. Thus, dialectical and historical materialism led our theoretical and methodological reflection to realize our goals, primary and secondary. We gave importance to the qualitative analysis, defining the bibliographical research, documentation, field, data and information collection, as being the main procedures of that research. The findings from this study allow us to affirm that the presence of higher education triggered changes in morphology and in the contents of the intraurbano space of Cajazeiras.